The Great Appreciation, the Great Depreciation, and the Purchasing Power Parity Hypothesis - David Papell (Oesterreichische Nationalbank (OeNB), 1998)
Although there has been much recent work on Purchasing Power Parity (PPP), neither univariate nor panel methods have produced strong rejections of unit roots in U.S. dollar real exchange rates for industrialized countries during the post-1973 period. We investigate the hypothesis that these non-rejections can be explained by one episode, the large appreciation and depreciation of the dollar in the 1980s, by developing unit root tests which account for this event and maintain long-run PPP. Using panel methods, we can reject the unit root null for those countries which adhere to the typical pattern of the dollar's rise and fall.
Keywords: 330